Insight into unsteady separated stagnation point flow of hybrid nanofluids subjected to an electro-magnetohydrodynamics Riga plate - Khashi’ie, Najiyah Safwa; Md Arifin, Norihan; Wahid, Nur Syahirah; Pop, Ioan (Multidisciplinary Digital Publishing Institute, 2023)
The main objective of this work is to analyze and compare the numerical solutions of an unsteady separated stagnation point flow due to a Riga plate using copper–alumina/water and graphene–alumina/water hybrid nanofluids. The Riga plate generates electro-magnetohydrodynamics (EMHD) which is expected to delay the boundary layer separation. The flow and energy equations are mathematically developed based on the boundary layer assumptions. These equations are then simplified with the aid of the similarity variables. The numerical results are generated by the bvp4c function and then presented in graphs and tables. The limitation of this model is the use of a Riga plate as the testing surface and water as the base fluid. The results may differ if another wall surfaces or base fluids are considered. Another limitation is the Takabi and Salehi’s correlation of hybrid nanofluid is used for the computational part. The findings reveal that dual solutions exist where the first solution is stable using the validation from stability analysis. Graphene–alumina/water has the maximum skin friction coefficient while copper–alumina/water has the maximum thermal coefficient for larger acceleration parameter. Besides, the single nanofluids (copper–water, graphene–water and alumina–water) are also tested and compared with the hybrid nanofluids. Surprisingly, graphene–water has the maximum skin friction coefficient while alumina–water has the maximum heat transfer rate. The findings are only conclusive and limited to the comparison between graphene–alumina and copper–alumina with water base fluid. The result may differ if another base fluid is used. Hence, future study is necessary to investigate the thermal progress of these hybrid nanofluids.